An Analysis of Adopting Social Media Marketing to Distribute Independent Films in the UK - Wang, Haiming (2015)
With the development of Internet and technology, independent film can be distributed in various methods even with low expenses. Social media could be considered as one of the leading ways of distributing independent films. This dissertation focuses on providing a deeper understanding of how social media has changed the way distributors develop marketing strategies for independent films. Semi-structured interview was used to conduct this research. This research gives distributors the most useful marketing mix and social media platforms for distributing independent films.